Implementation of the psychowriting methods to improve linguistic intelligence for children in the field of writing interest - Kalida, Muhsin; AD, yahya (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
Increasing children's intelligence requires strategies so that children have the habit of reading and writing things. One strategy that can be used is psychowriting. The purpose of this study was to increase the spirit of children with literacy to have enthusiasm for writing and interest in reading using the psychowriting method. This research is field research with a qualitative descriptive analysis approach. Data collection methods, using observation, interviews and documentation. The results of this study indicate that the implementation of psychowriting methods to improve linguistic intelligence for children is: a) preparation, b) memory strength test, c) presenting the closest and fastest idea, d) creating an atmosphere, e) implementing creative learning, and f) follow-up.